2002
DOI: 10.1176/appi.ajp.159.9.1603
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation, Childhood Trauma, andAtaque De NerviosAmong Puerto Rican Psychiatric Outpatients

Abstract: Frequent ataques de nervios may, in part, be a marker for psychiatric disorders characterized by dissociative symptoms. Childhood trauma per se did not account for ataque status in this group of female outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 9 publications
7
54
0
Order By: Relevance
“…Ataque phenomenology may contribute to the salience in Caribbean Latinos of trembling, uncontrollable crying and/or screaming, aggressive or suicidal behavior, and depersonalization/derealization symptoms, during acute anxiety episodes that meet PA criteria. [25,36,38] Finally, feelings of heat in specific parts of the body (head, chest, neck) are common across several cultural groups during PAs and are not well captured by the phrase "hot flushes," which suggest full body heat sensations. [26,30] Fifty-three percent of ataques, for example, are characterized by "a sense of heat rising in the chest."…”
Section: Panic Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Ataque phenomenology may contribute to the salience in Caribbean Latinos of trembling, uncontrollable crying and/or screaming, aggressive or suicidal behavior, and depersonalization/derealization symptoms, during acute anxiety episodes that meet PA criteria. [25,36,38] Finally, feelings of heat in specific parts of the body (head, chest, neck) are common across several cultural groups during PAs and are not well captured by the phrase "hot flushes," which suggest full body heat sensations. [26,30] Fifty-three percent of ataques, for example, are characterized by "a sense of heat rising in the chest."…”
Section: Panic Attackmentioning
confidence: 99%
“…In many cultures, PAs are expected after traumatic exposures, reducing the likelihood that these attacks would meet PD criteria, as they would be attributed to the traumatic experience. [26,38] Postattack negative sequelae of at least one month duration: In one study, 80% of Caribbean Latino psychiatric outpatients with ataques de nervios endorsed at least one of the three postattack sequelae included in PD criterion A2, [36] suggesting that this criterion adequately captures the consequences of a panic-like episode in this cultural group. However, more research is necessary on its cross-cultural validity.…”
Section: What Is the Cross-cultural Validity Of Existing Panic Disordmentioning
confidence: 99%
“…That is, a Puerto Rican patient may experience dissociation in this culturally specific form. One recent study [Lewis-Fernández et al, 2002] of 29 Puerto Rican patients found the severity of dissociation (as assessed by the Dissociative Experiences Scale [DES]) to be significantly associated with the lifetime frequency of ataque de nervios.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to emphasize the fragmentation of identity, memory, and consciousness but to add several features: the disruptive effect of such symptoms on consciousness and a broader definition of symptoms (including examples from non-Western cultures, such as possession; Dell, 2002;Korol, 2008;Lewis-Fernandez et al, 2002). Amnesia would continue to be a diagnostic requirement.…”
Section: Spiegelmentioning
confidence: 99%